Betaine delays age‐related muscle loss by mitigating Mss51‐induced impairment in mitochondrial respiration via Yin Yang1 - Si Chen; Tongtong He; Jiedong Chen; Dongsheng Wen; Chen Wang; Wenge Huang; Zhijun Yang; Mengtao Yang; Mengchu Li; Siyu Huang; Zihui Huang; Huilian Zhu (Wiley, 2024)
Abstract Background Mitochondrial dysfunction is one of the hallmarks of aging and a leading contributor to sarcopenia. Nutrients are essential for improving mitochondrial function and skeletal muscle health during the aging process. Betaine is a nutrient with potential muscle‐preserving properties. However, whether and how betaine could regulate the mitochondria function in aging muscle are poorly understood. We aimed to explore the molecular target and underlying mechanism of betaine in attenuating the age‐related mitochondrial dysfunction in skeletal muscle. Methods Young mice (YOU, 2 months), old mice (OLD, 15 months), and old mice with betaine treatment (BET, 15 months) were fed for 12 weeks. The effects of betaine on muscle mass, strength, function, and subcellular structure of muscle fibres were assessed. RNA sequencing (RNA‐seq) was conducted to identify the molecular target of betaine. The impacts of betaine on mitochondrial‐related molecules, superoxide accumulation, and oxidative respiration were examined using western blotting (WB), immunofluorescence (IF) and seahorse assay. The underlying mechanism of betaine regulation on the molecular target to maintain mitochondrial function was investigated by luciferase reporter assay, chromatin immunoprecipitation and electrophoretic mobility shift assay. Adenoassociated virus transfection, succinate dehydrogenase staining (SDH), and energy expenditure assessment were performed on 20‐month‐old mice for validating the mechanism in vivo. Results Betaine intervention demonstrated anti‐aging effects on the muscle mass (P = 0.017), strength (P = 0.010), and running distance (P = 0.013). Mitochondrial‐related markers (ATP5a, Sdha, and Uqcrc2) were 1.1‐ to 1.5‐fold higher in BET than OLD (all P ≤ 0.036) with less wasted mitochondrial vacuoles accumulating in sarcomere. Bioinformatic analysis from RNA‐seq displayed pathways related to mitochondrial respiration activity was higher enriched in BET group (NES = −0.87, FDR = 0.10). The quantitative real time PCR (qRT‐PCR) revealed betaine significantly reduced the expression of a novel mitochondrial regulator, Mss51 (−24.9%, P = 0.002). In C2C12 cells, betaine restored the Mss51‐mediated suppression in mitochondrial respiration proteins (all P ≤ 0.041), attenuated oxygen consumption impairment, and superoxide accumulation (by 20.7%, P = 0.001). Mechanically, betaine attenuated aging‐induced repression in Yy1 mRNA expression (BET vs. OLD: 2.06 vs. 1.02, P = 0.009). Yy1 transcriptionally suppressed Mss51 mRNA expression both in vitro and in vivo. This contributed to the preservation of mitochondrial respiration, improvement for energy expenditure (P = 0.008), and delay of muscle loss during aging process. Conclusions Altogether, betaine transcriptionally represses Mss51 via Yy1, improving age‐related mitochondrial respiration in skeletal muscle. These findings suggest betaine holds promise as a dietary supplement to delay skeletal muscle degeneration and improve age‐related mitochondrial diseases.